ASSOCIATION BETWEEN MATERNAL QUALITY OF LIFE AND NUTRITIONAL STATUS OF UNDER-FIVE CHILDREN IN A COASTAL COMMUNITY OF KOLLAM DISTRICT, KERALA: A CROSS-SECTIONAL STUDY (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Malnutrition among under five children continues to be a serious public health problem in the world and is a major contributing factor for childhood morbidity and mortality. Maternal factors such as education, socioeconomic status, nutritional status and quality of life are important determinants of health and nutritional outcomes of the children. There is limited evidence on association of maternal quality of life and nutritional status of under-five children in coastal communities of Kerala. Aims & Objectives 1.    To assess the quality of life of mothers of under-five children in Jonakapuram, a Coastal Community of Kollam District, Kerala. 2.    To assess the nutritional status of under-five children. 3.    To determine the association between maternal quality of life and nutritional status of under-five children. Methodology: A community based cross sectional study was conducted among 141 mothers and their under five children residing in Jonakapuram, a Coastal Community of Kollam District, Kerala. Participants were selected using simple random sampling from the current Health Management Information System records. Data was collected using a pretested structured questionnaire including sociodemographic details, WHOQOL-BREF questionnaire and anthropometric assessment of children. Nutritional status was evaluated using WHO Growth Standards. The data were entered into Microsoft Excel and analyzed using appropriate statistical software. Chi-square test was used to find the association between maternal quality of life domains and nutritional status of children. Results: Among the 141 mothers studied, 78.0% were aged 20–30 years and 51.1% had high-school education. Most mothers were homemakers (90.1%) and belonged to households with a monthly income below ₹5000 (62.4%). Moderate and severe stunting were observed among 21.3% and 12.1% of children, respectively. Moderate and severe underweight were observed among 22.7% and 9.9% of children, respectively. Most mothers had average scores in the physical (73.8%), psychological (63.8%), social relationship (63.1%), and environmental (61.7%) domains of WHOQOL-BREF. A statistically significant association was observed between the social relationship domain of maternal quality of life and children's nutritional status (χ² = 23.361, p = 0.025). No significant association was found between physical, psychological, or environmental domains and nutritional status. Conclusions: A considerable proportion of under-five children in the study area were affected by stunting and underweight. Maternal social relationship quality showed a significant association with the nutritional status of children. Strengthening maternal social support systems and improving maternal well-being may contribute to better child nutritional outcomes.